Entrepreneurial commitment, entrepreneurial competence, towards business performance through business competitiveness development - Tri Sulkarnain Ahmad; Srifatmawati Ahmad; Afriyani Afriyani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Wajo Regency is the best silk weaving industrial area in South Sulawesi, but the emergence of several competitors for silk fabrics from abroad, and various modern-style fabric products that are variously supplied by wholesalers from outside the South Sulawesi area indirectly affect the movement of market. This study aims to determine the effect of entrepreneurial commitment, entrepreneurial competence and competitiveness of the silk industry on the business performance of silk entrepreneurs. The type of research is a quantitative research methodology. The research was conducted on a silk business located in Wajo Regency, South Sulawesi Province. A total of 357 samples were obtained using the cluster random sampling technique based on the Krejcie and Morgan tables. Data collection method employing a scale that uses the Likert scale. Data analysis techniques using the SmartPLS 3.0 software's path analysis, it was found that commitment, entrepreneurial competence has a significant effect on business performance, commitment has a significant effect on the development of competitiveness, and entrepreneurial competence has not significant effect on the development of competitiveness. The results found that the entrepreneurial competence of silk entrepreneurs was still lacking in developing the competitiveness of the silk business.